EVALUASI PENERAPAN STANDAR AUDIT TERKAIT BUKTI (SA 500) PADA DOKUMEN PEMBELIAN DALAM PEMERIKSAAN LAPORAN KEUANGAN DI KANTOR AKUNTAN PUBLIK - Ardana Febrianto (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Abstract:This study essentially aims to measure the extent to which SA 500 on audit evidence is actually implemented in the field, specifically when auditors examine purchasing documents at public accounting firms. The approach is descriptive and qualitative, not counting numbers, but rather examining the procedures, sufficiency, and reliability of the evidence collected from purchasing transactions. What was found was quite thought-provoking. Documents such as invoices, purchase orders, and receipts are indeed the backbone of audit evidence. But yes, there are problems too. Document completeness is often incomplete, and the issue of reliability is also unclear, especially when the documents come from within the entity itself because, well, who wants to be honest with themselves? Furthermore, procedures such as inspection, confirmation, and analysis are not yet optimal. There is a gap between what should be and what actually happens. In conclusion, auditors need to be sharper in their professional judgment andtheir audit procedures must be strengthened to align with SA 500, ultimately improving overall audit quality.Keywords: audit evidence; purchasing documents; public accounting firm; SA 500; auditing standards